Hypercholesterolemia Correlates With Glomerular Phospholipase A2 Receptor Deposit and Serum Anti-Phospholipase A2 Receptor Antibody and Predicts Proteinuria Outcome in Idiopathic Membranous Nephropathy - Dong, Lei; Li, Yue-qiang; Guo, Shui-ming; Xu, Gang; Wei, Wang; Han, Min (Frontiers in Immunology, 2022)
Background The anti-phospholipase A2 receptor (PLA2R) antibody is a non-invasive diagnostic tool and prognosis predictor of idiopathic membranous nephropathy (IMN). Baseline hypercholesterolemia independently predicts proteinuria outcomes in IMN patients. Thus, we investigated whether hyperlipidemia is correlated with anti-PLA2R and pathological indicators. Methods A total of 495 IMN patients identified by kidney biopsy in Wuhan Tongji Hospital, China, from January 2016 through December 2020 were enrolled in this study. Data on clinical features, pathology findings, and outcomes were collected. Results Total cholesterol (TC), non-high-density lipoprotein cholesterol (non-HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglyceride (TG) were positively related to proteinuria, indicating damage to the renal glomerulus [Spearman’s rank correlation coefficient = 0.432, 0.462, 0.315, and 0.289, respectively, P < 0.001 for all]. In univariate logistic regression, low HDL-C [odds ratio (OR): 0.856; 95% CI: 0.778–0.939; P = 0.001] and high TG [OR: 1.025; 95% CI: 1.006–1.044; P = 0.011] were correlated with tubular atrophy, suggesting lesions on tubules. Increased TC [adjusted OR: 1.285; 95% CI: 1.119–1.475; P < 0.001], non-HDL-C [adjusted OR: 1.284; 95% CI: 1.113–1.482; P = 0.001], and LDL-C [adjusted OR: 1.178; 95% CI: 1.009–1.376; P = 0.039] independently predicted glomerular PLA2R deposit; similar results were observed for lipids in predicting the seropositivity of anti-PLA2R antibodies. After treatment, increased HDL-C [adjusted hazard ratio (HR): 1.764; 95% CI: 1.241–2.507; P = 0.002] and decreased non-HDL-C [adjusted HR: 0.884; 95% CI: 0.795–0.983; P = 0.022] independently predicted proteinuria remission. Conclusion Hypercholesterolemia is a potentially useful biomarker for disease severity, serum anti-PLA2R antibody, glomerular PLA2R deposit, and proteinuria outcome of IMN.